2016
DOI: 10.4172/pharmaceutical-sciences.1000136
|View full text |Cite
|
Sign up to set email alerts
|

Can Galantamine Act as an Antidote for Organophosphate Poisoning? A Review

Abstract: Indu, et al.: Galantamine in the Management of Organophosphate PoisoningOrganophosphate compounds are commonly used as insecticides in rural areas and powerful warfare agents by military personnel. These agents inhibit cholinesterases especially acetylcholinesterase and accumulate acetylcholine causing muscarinic, nicotinic and central nervous system manifestations. Currently, drugs such as atropine, oximes and benzodiazepine are used to treat these symptoms. But these drugs are associated with certain drawbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In some studies, Rivastigmine revealed high inter-patient variability because of its complex pharmacological profile ( Lavon et al, 2015 ; Park et al, 2018 ). Furthermore, Galantamine, based on some preclinical studies, seems to be potent and effective with low toxicity ( Indu et al, 2016 ). Other animal investigations have demonstrated the efficacy of drugs like as Galantamine, Physostigmine, Trihexyphenidyl, Benactyzine, and Procyclidine; however, in anticonvulsant doses against Soman, they all resulted in behavioral impairments ( Myhrer and Aas, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, Rivastigmine revealed high inter-patient variability because of its complex pharmacological profile ( Lavon et al, 2015 ; Park et al, 2018 ). Furthermore, Galantamine, based on some preclinical studies, seems to be potent and effective with low toxicity ( Indu et al, 2016 ). Other animal investigations have demonstrated the efficacy of drugs like as Galantamine, Physostigmine, Trihexyphenidyl, Benactyzine, and Procyclidine; however, in anticonvulsant doses against Soman, they all resulted in behavioral impairments ( Myhrer and Aas, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…This in turn would help in designing a better evidence-based therapy. 13 Recent evidence suggests the use of galantamine in OP poisoning cases. Galantamine is an irreversible competitive inhibitor of AChE and up lights the possible outcomes of galantine use in OP poisoning.…”
mentioning
confidence: 99%
“…Furthermore, the property of Galantamine in the prevention of neurodegeneration is ideal for OP poisoning cases. 13 However, atropine and pralidoxime have been widely employed for intoxication. Atropine competitively antagonizes acetylcholine only at muscarinic receptors while being ineffective on the nicotinic receptors attributing to its inefficacy in the prevention of clinical manifestations involving muscle weakness, 14 respiratory depression, convulsion and coma where supportive care should be initiated.…”
mentioning
confidence: 99%